Information and Communication Technology Based Education Marketing Management - Afifah, Isna Zahrotun; Wiyani, Novan Ardy (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2022)
This study aimed to describe information and communication (ICT)-based education marketing management in MTs Ma’arif NU 1 Jatilawang Banyumas. This study employed qualitative approach by using interview, observation, and documentation for the data collection. The collected data were analyzed by Miles and Huberman model, consisted of data reduction, data presentation and data verification. The results of the study shows that education marketing management in MTs Ma’arif NU 1 Jatilawang Banyumas utilized information and communication technology (ICT), especially in its education marketing. In this study, the education marketing was done by George R. Terry’s theory in management function analysis which were planning, organization, implementation, and evaluation. ICT-based education marketing management in MTs Ma’arif NU 1 Jatilawang Banyumas was done through ICT-based planning of education marketing management, ICT-based organization of education marketing management, ICT-based implementation of education marketing management, and ICT-based evaluation of education marketing management.